The effect of adding ZrO2 nanoparticles on the transverse strength and hardness of microwave-cured acrylic and heat-cured acrylic denture base materials - Shehab, Marwah M.; Hasan, Radhwan Himmadi; Aziz, Rana Rabee (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: One drawback of acrylic denture base materials is their liability to fracture, requiring methods to increase fracture resistance. Adding nanoparticles (NPs) represented one of these methods. Purpose: The objectives of this study are to evaluate and compare transverse strength and hardness when adding zirconium oxide nanoparticles (ZrO2 NPs) at concentrations of 0%, 3%, and 5% to heat-cured acrylic denture base materials (Ivoclare, Major) and to microwave-cured acrylic (Acron MC). Methods: Transverse strength was tested with a Universal Testing Machine (GESTER, Fujian, China), while hardness tests were conducted by using a Shore-D hardness durometer (Show, China). The 90 samples were prepared and then divided into three groups for each material. Attenuated total reflectance–Fourier transform infrared (ATR-FTIR) spectroscopy was used to analyze the microstructure. The samples were prepared following the manufacturer’s instructions for each material. Results: The results revealed that the addition of ZrO2 NPs (3%, 5%) improves the transverse strength and hardness of polymethyl methacrylate acrylic resin for both types (microwave-cured and heat-cured acrylic resins). The addition of ZrO2 NPs at 3% concentration shows the highest values for both transverse strength and hardness. The ATR-FTIR confirms no structural chemical changes with the addition of ZrO2 NPs. Conclusion: The study concludes that the incorporation of ZrO2 NPs (3%, 5%) into microwave-cured and heat-cured acrylic resins improves transverse strength and hardness.